Pengaruh Kepuasan Kerja dan Kompensasi terhadap Intention to Stay dengan Komitmen Organisasi sebagai Variabel Intervening - Dini Shelvia Monica; Anton Prasetyo (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The purpose of this study was to determine the effect of job satisfaction and compasation on intention to stay with organizational commitment as an intervening variable. The sampling method used in this study nonprofit sampling with purposive technique. The total sample in this study was 40 respondents. The method of collecting data using a questionnaire. The data analysis used was the validity and reliability instrument, the classical assumption test, hypothesis test and path analysis using the SPSS 25 for windows program. The results of this study indicate that all items of each variable are valid and reliable. The first model fulfills the criteria for the classical assumption test with no multicolonierity, heteroscedasticity, and fulfills the normality assumption, but in the second model there is multicolonierity. Based on the t test, it shows that job satisfaction and compensation have a significant effect on organizational commitment, job satisfaction and compensation have a significant effect on intention to stay, organizational commitment has a significant effect on intention to stay.